Effects of prostaglandin E1, melatonin, and oxytetracycline on lipid peroxidation, antioxidant defense system, paraoxonase (PON1) activities, and homocysteine levels in an animal model of spinal cord injury - Topsakal, C; Kilic, N; Ozveren, F; Akdemir, I; Kaplan, M; Tiftikci, M; Gursu, F (Lippincott Williams & Wilkins, 2003)
Study Design. Investigation of the effects of prostaglandin E1, melatonin, and oxytetracycline on lipid peroxidation, antioxidant and paraoxonase activities, and homocysteine levels in an experimental model of spinal cord injury. Objectives. To determine the antioxidant efficacy of prostaglandin E1, melatonin, and oxytetracycline and whether paraoxonase and homocysteine can be used as monitoring parameters in the acute oxidative stress of spinal cord injury. Summary of Background Data. Melatonin has been found useful in spinal cord injury in previous studies. No study exists investigating the effects of melatonin, prostaglandin E1, and oxytetracycline as well as the response type of paraoxonase enzyme and homocysteine levels in the acute oxidative stress of spinal cord injury. Methods. Sixty-three male albino Wistar rats were anesthetized with 400 mg/kg chloral hydrate and divided into 5 groups. The G1 ( n = 7) control group provided the baseline levels. G2 - G5 underwent T3 - T6 total laminectomies and spinal cord injuries by clip compression at the T4 - T5 levels. Medications were applied to G3 - G5 right after clip compression. Hence, G2 constituted laminectomy + injury, G3 laminectomy + injury + prostaglandin E1; G4 laminectomy + injury + melatonin, and G5 laminectomy + injury + oxytetracycline groups. Animals were decapitated either the first or fourth hour after injury. Spinal cord tissue and blood malonyldialdehyde and plasma homocysteine levels, plasma glutathione peroxidase, superoxide dismutase, paraoxonase activities were assayed. The SPSS 9.0 program was used for statistical analysis and graphics. Intergroup comparisons were made by Bonferroni corrected Mann Whitney U test ( P < 0.025) and intragroups comparisons by Wilcoxon Rank test ( P < 0.03). Results. In injury groups, plasma homocysteine levels decreased and paraoxonase activities increased as erythrocyte superoxide dismutase levels and plasma glutathione peroxidase activities decreased in parallel to increases of tissue and blood malonyldialdehyde levels. These alterations were relatively suppressed by prostaglandin E1, melatonin, and oxytetracycline administrations in varying degrees. Melatonin was the most powerful agent, particularly at the fourth hour. Oxytetracycline was also effective, both at the first and fourth hour. Prostaglandin E1 was effective in comparison to injury group, but not as much as melatonin and oxytetracycline. Conclusions. Melatonin and oxytetracycline are effective in preventing lipid peroxidation in spinal cord injury. Paraoxonase and homocysteine can be used in monitoring the antioxidant defense system as well as superoxide dismutase and plasma glutathione peroxidase, both in injury and medicated groups.
Keywords: antioxidant drugs; homocysteine; lipid peroxidation; paraoxonase; spinal cord injury